Large-scale UAV-Network using the Hata - Okumura model with PSO algorithm for Open Area Communication - Sarfo, Kwame; Wang, Kehao; F, Miora Rakotomandimby; Ntiamoah-Sarpong, Kwadwo (2021 International Conference on Computer Engineering and Artificial Intelligence (ICCEAI), 2021)
Unmanned aerial vehicles (UAVs) continue to play a vital role in many domains, such as agriculture, service delivery, photo shooting, disaster management, telecommunication, and other spheres of life. It can also be employed as aerial base stations to serve low wireless Fidelity (Wi-Fi) signal strength in inaccessible areas such as mountainous areas, valleys, and forests, challenging to install landline communication infrastructure. This paper considers UAVs as base stations to serve numerous users in an accessible region based on the Hata - Okumura (231model) in open space to study the path loss. Employing the particle swarm optimization (PSO) algorithm simulation results, it was clear that the appropriate number of UAVs required in a given open area could be easily determined based on the antenna range of each UAV. Eight 200m range UAVs were able to provide coverage of 26%. Similar sets of 400m range UAVs provided 69% and with the 500m range covering 87% of the entire field. It is noted that the coverage could be increased by increasing the number of UAVs or adopting a higher antenna range of UAVs.